BCG vaccination potential for COVID-19: an analytical approach - Mina T. Kelleni (Taylor & Francis Group, 2021)
In order to assess the possible protective potential of BCG vaccination as regards to COVID-19, we have analyzed BCG vaccination status and SARS CoV-2 morbidity and mortality in China and we have also examined other studies performed in other countries to assess the potential of booster doses of BCG vaccination for adults. We have concluded that BCG vaccination early in life is highly unlikely to be a tool that might prevent SARS CoV-2 infection in adults. Furthermore, we have suggested that BCG vaccination potential benefit to decrease COVID-19 morbidity and mortality in children is confounded by many factors, e.g. age limitations of exposure and other vaccines. However, BCG vaccination booster doses in adults might be of protective value until the results of well-designed clinical trials are published to confirm, or refute, this potential.